Polymer-ceramic integrated lithium battery diaphragm coating as well as preparation method and application thereof
By coating polymer-ceramic integrated materials on the lithium battery separator and combining thickener and binder, the shortcomings in the existing separator coating in terms of wetting ability and bonding properties are solved, and the thermal stability, wetting properties and mechanical properties of the separator are improved.
Patent Information
- Application Number
- CN202510030267.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium battery separator coating has limited effect in improving the separator wetting ability, and the adhesion performance between the separator and the battery electrode is poor.
Using polymer-ceramic integrated materials, the wetting performance of the membrane to the electrolyte and the adhesive properties of the membrane are improved by coating the modified ceramic and polymer on the membrane, combining thickener and binder.
It significantly improves the thermal stability, wetting and mechanical properties of the diaphragm, improves the permeability of the electrolyte and the adhesive strength of the electrode sheet, and improves the overall performance of the battery.
Smart Images

Figure CN119833885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a polymer-ceramic integrated lithium battery diaphragm coating and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used as power sources for electronic devices and new energy vehicles due to their excellent energy consumption performance. The diaphragm plays an important role in lithium-ion batteries. Its main function is to effectively transfer ion carriers between electrodes as an electrolyte reservoir and an efficient ion conductor, and to prevent electrical contact between electrodes as a good electrical insulator. The safety and high efficiency of lithium batteries are closely related to the performance and structure of the diaphragm. As an electrolyte reservoir, the diaphragm needs to have a high porosity and air permeability, and it is necessary to ensure that the diaphragm and the battery electrodes are firmly bonded. Therefore, it is of great significance to develop a diaphragm with good bonding properties and air permeability.
[0003] Polyolefin materials have low surface energy and poor wettability with electrolytes. This phenomenon directly leads to the inability of the pores of the battery separator to be fully filled with electrolytes, which in turn has a significant impact on the overall performance of the battery. In order to effectively improve the wettability of the separator to the electrolyte, the most direct and effective strategy is to perform surface coating modification on the separator to form a coating on the surface of the separator. However, the current separator coating has very limited ability to improve the separator's wettability, and the resulting separator has poor bonding performance with the battery electrode. Summary of the invention
[0004] The present invention proposes a polymer-ceramic integrated lithium battery diaphragm coating and a preparation method and application thereof, which solves the problem in the related art that the diaphragm coating has very limited ability to enhance the diaphragm wetting ability and that the prepared diaphragm has poor bonding performance with the battery electrode.
[0005] The technical solution of the present invention is as follows: The polymer-ceramic integrated lithium battery separator coating comprises modified ceramic and polymer; or ceramic and modified polymer; or modified ceramic and modified polymer; the modifiers in the modified ceramic and modified polymer each independently comprise aromatic ring compounds containing hydroxyl and carboxyl groups.
[0006] As a further technical solution, it also includes at least one of the following features: a thickener and a binder.
[0007] In the present invention, a thickener and / or a binder is further added to further improve the wettability between the diaphragm and the electrolyte, and the bonding performance between the diaphragm and the pole piece.
[0008] As a further technical solution, the thickener includes one or more of sodium carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, and lithium carboxymethyl cellulose.
[0009] As a further technical solution, the thickener is added to water at a concentration of 2 wt %, and the obtained solution has a viscosity of 400-800 cp at 25° C.
[0010] As a further technical solution, the binder includes a water-based binder and PVDF.
[0011] In the present invention, the aqueous binder and PVDF are used together as a binder, and PVDF provides good ionic conductivity, extremely high chemical stability and excellent bonding performance.
[0012] As a further technical solution, the aqueous binder includes one or more of polyvinyl alcohol, polyvinyl butyral, polyacrylic acid, and styrene-butadiene rubber.
[0013] As a further technical solution, the viscosity of the aqueous binder is 7300-9300 mpa·s and the solid content is 15%-25%.
[0014] As a further technical solution, it includes modified ceramics and modified polymers in a mass ratio of 1:2 to 2:1.
[0015] The battery separator coating of the present invention comprises modified ceramics and modified polymers in a mass ratio of 1:2 to 2:1, which further improves the wetting performance between the separator and the electrolyte, and the bonding performance between the separator and the pole piece.
[0016] As a further technical solution, the preparation method of the modified ceramic comprises the following steps: mixing ceramic, a modifier and water, performing modification, and drying to obtain the modified ceramic.
[0017] As a further technical solution, the modification temperature is 50-60°C.
[0018] As a further technical solution, the mass ratio of water to ceramic is 10~50:1.
[0019] As a further technical solution, the preparation method of the modified polymer comprises the following steps: after mixing the polymer, water and ammonia water, adding a modifier for modification, and drying to obtain the modified polymer.
[0020] As a further technical solution, suction filtration and washing are performed before drying.
[0021] As a further technical solution, the washing is specifically water washing.
[0022] As a further technical solution, the modification temperature is 50-60°C.
[0023] As a further technical solution, the mass ratio of water, aqueous ammonia and polymer is 10~50:0.05~0.3:1.
[0024] As a further technical solution, when modified ceramics are included, the raw materials of the modified ceramics include ceramics and modifiers in a mass ratio of 1:0.1-0.5; When a modified polymer is included, the raw materials of the modified polymer include a polymer and a modifier in a mass ratio of 1:0.05-0.5.
[0025] As a further technical solution, the aromatic ring compound containing hydroxyl and carboxyl groups includes one or more of 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 4,5-dihydroxyisophthalic acid, and 4,4'-oxybis(3-hydroxybenzoic acid).
[0026] The CAS number of 4,4'-oxybis(3-hydroxybenzoic acid) is 20105-29-7.
[0027] As a further technical solution, when the modified ceramic is included, the ceramic in the modified ceramic includes porous ceramic and / or non-porous ceramic; As a further technical solution, the porous ceramic includes one or more of porous alumina, porous boehmite, porous barium sulfate, porous aluminum sulfate, porous titanium dioxide, porous aluminum nitride, porous magnesium nitride, porous magnesium hydroxide, porous molybdenum disulfide, and porous barium titanate.
[0028] As a further technical solution, the non-porous ceramic includes one or more of alumina, boehmite, barium sulfate, aluminum sulfate, titanium dioxide, aluminum nitride, magnesium nitride, magnesium hydroxide, molybdenum disulfide, and barium titanate.
[0029] When a modified polymer is included, the polymer in the modified polymer includes one or more of styrene acrylate copolymer particles, polymethyl methacrylate particles, poly(vinyl chloride-co-vinyl acetate) particles, polyethylene particles, and polyacrylic acid particles.
[0030] As a further technical solution, when the modified ceramic is included, the raw material of the modified ceramic also includes a solvent; When a modified polymer is included, the raw materials of the modified polymer also include a solvent and an alkaline auxiliary agent; The solvent in the raw material of the modified ceramic and the solvent in the raw material of the modified polymer each independently include one or more of water, N,N-dimethylacetamide, N-methylpyrrolidone, hexamethylphosphoramide, 1,4-dioxane, diglyme, and N,N-dimethylformamide; The alkaline auxiliary agent includes one or more of ammonia water, dimethylamine, triethylamine, aniline and pyridine.
[0031] The present invention also proposes a method for preparing the polymer-ceramic integrated lithium battery separator coating, comprising the following steps: When modifying ceramics and polymers, the following steps are involved: S1, mixing the modified ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; When ceramic and modified polymer are involved, the following steps are involved: S1, mixing ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the modified polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; S6, coating the slurry on the surface of the base film, and drying to obtain a polymer-ceramic integrated lithium battery separator coating; When including modified ceramics and modified polymers, the following steps are included: S1, mixing the modified ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the modified polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; S6. Apply the slurry on the surface of the base film and dry it to obtain a polymer-ceramic integrated lithium battery separator coating.
[0032] As a further technical solution, the mass ratio of the water, modified ceramic, thickener, PVDF and binder is 10:1~2:0.2:0.5:0.2.
[0033] As a further technical solution, the mass ratio of the water, ceramic, thickener, PVDF and binder is 10:1~2:0.2:0.5:0.2.
[0034] As a further technical solution, the temperatures of the first emulsification, the second emulsification and the fourth emulsification are each independently 50-60°C, the time is each independently 30-40 min, the rotation speed is each independently 1800-2000 r / min, and the revolution speed is each independently 40-50 r / min.
[0035] As a further technical solution, the temperature of the third emulsification and the fifth emulsification are independently 50-60°C, the time is independently 20-30 min, the rotation speed is independently 800-1000 r / min, and the revolution speed is independently 40-50 r / min.
[0036] As a further technical solution, the first emulsification, the second emulsification, the third emulsification, the fourth emulsification and the fifth emulsification are all carried out under a vacuum environment, and preferably the vacuum degree is -0.095~-0.08MPa.
[0037] The present invention also proposes a battery separator, comprising a base film and the polymer-ceramic integrated lithium battery separator coating arranged on at least one side of the base film or the polymer-ceramic integrated lithium battery separator coating prepared by the preparation method.
[0038] The present invention not only significantly improves the thermal stability of the diaphragm by coating the ceramic-polymer integrated material on the base film, so that it can remain stable in a high temperature environment; at the same time, it also greatly improves the wettability of the electrolyte, so that the electrolyte can more fully penetrate into the interior of the diaphragm, and has excellent electrolyte absorption capacity; in addition, it also significantly enhances the mechanical properties of the diaphragm, so that it can withstand greater pressure and deformation during battery assembly and use, opening up a new way to improve the performance of the battery diaphragm. In addition, the battery diaphragm provided by the present invention also has good dimensional stability and flexibility, and can be firmly in contact with the electrodes.
[0039] The present invention also provides a battery, comprising the polymer-ceramic integrated lithium battery diaphragm coating or the polymer-ceramic integrated lithium battery diaphragm coating prepared by the preparation method or the battery diaphragm.
[0040] The battery in the present invention can be any electrochemical device in the art, for example, a lithium battery, a lithium-sulfur battery, etc., preferably a lithium battery.
[0041] The working principle and beneficial effects of the present invention are: 1. The polymer-ceramic integrated lithium battery separator coating of the present invention cleverly combines the dual advantages of inorganic and organic materials: the organic component of the coating gives it excellent flexibility and good adhesion to the separator, ensuring stability under various conditions of use; while the inorganic component of the coating significantly enhances the wettability and mechanical properties of the separator, enabling it to perform well even under extreme conditions such as high temperature and high pressure.
[0042] 2. The polymer-ceramic integrated lithium battery separator coating of the present invention has the properties of both ceramic coating and polymer coating, and the ceramic has a high porosity. After being modified with an aromatic ring compound containing hydroxyl and carboxyl groups, the wettability of the separator can be improved. In addition, the polymer modified with an aromatic ring compound containing hydroxyl and carboxyl groups is easier to disperse, has good electrolyte affinity, can be used for point bonding with good adhesion, has little effect on ion transmission channels, and has excellent electrochemical properties.
[0043] 3. The polymer-ceramic integrated lithium battery diaphragm coating of the present invention includes modified ceramics and polymers; or, includes ceramics and modified polymers; or, includes modified ceramics and modified polymers. By modifying the ceramics and / or polymers, there is no need to add the traditional dispersant, which reduces the cost, and the modified ceramics and polymers can be well dispersed in the system. The modified ceramics can enhance the liquid absorption and retention of the diaphragm while also increasing the thermodynamic properties of the diaphragm through the introduction of an aromatic ring skeleton. After modification, the polymer can be better dispersed in the slurry, and can also increase the intermolecular van der Waals force, thereby enhancing the adhesion between the diaphragm and the electrode.
[0044] 4. The polymer-ceramic integrated lithium battery separator coating of the present invention has good thermal stability. Even in a high temperature environment, it can maintain excellent dimensional stability and effectively resist high temperature shrinkage, thereby greatly improving the mechanical strength of the separator and ensuring that it remains indestructible when subjected to external force impact. The coating also has excellent electrolyte affinity and can significantly improve the wetting performance between the separator and the electrolyte. This feature helps to optimize the ion conduction efficiency, further reduce the internal resistance of the battery, and achieve more efficient energy conversion. In addition, its bonding performance is particularly outstanding, ensuring the bonding of the separator and the pole piece. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0046] Figure 1 This is a SEM image of the slurry of Example 3 of the present invention at 100 times magnification; Figure 2 This is a SEM image of the slurry of Example 3 of the present invention at a magnification of 10,000 times. DETAILED DESCRIPTION
[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The parameters of the raw materials in the following examples and comparative examples are as follows: The polyolefin base film is a wet-process polyethylene film. The thickness of the base film tested by the method in GB / T 36363-2018 is 7.1 μm and the air permeability is 71 Sec / 100 mL. Base films of other thicknesses may also be used. The coating weight of the slurry is 0.5g / m 2 ; The weight average molecular weight of PVDF is 78.8w and the melting point is 150.1℃; The particle size D50 of porous alumina is 0.6~0.8μm, and the specific surface area is 15~20m 2 / g, porosity is 30%~45%; The non-porous alumina was conventional alumina powder with a particle size D50 of 0.6-0.8 μm, purchased from Luoyang Zhongchao New Materials Co., Ltd. The particle size D50 of the styrene acrylate copolymer particles is 4.2 μm, the number average molecular weight is 123598, and the particles are copolymerized by styrene and acrylate in a molar ratio of 1:3; Sodium carboxymethyl cellulose is a light yellow powder with a viscosity of 400~800cp (2wt% dissolved in water at 25℃); Polyacrylic acid is a solution with a solid content of 25% and a viscosity of 7300~9300mpa·s; Polyvinyl alcohol is a solution with a solid content of 15% and a viscosity of 7300~9300mpa·s.
[0049] Example 1 S1. Add porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid into a synthesis reactor, stir at 60° C. and 30 r / min for 30 min, and then dry to obtain modified porous alumina; the mass ratio of porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.2; S2. Add deionized water and modified porous alumina into a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), mix and emulsify to obtain a first substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and in a vacuum environment; the vacuum degree of the vacuum environment is -0.095 MPa; S3, adding the first substance and styrene acrylate copolymer particles to an emulsification tank, mixing, emulsifying, and obtaining a second substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S4, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, and obtaining a third substance; the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S5, mixing the third substance and PVDF, emulsifying, and obtaining a fourth substance; the emulsification conditions are: stirring for 40 min at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.080 MPa; S6, mixing the fourth substance and polyvinyl alcohol, emulsifying, and obtaining a slurry; the emulsification conditions are: stirring for 30 min at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; In the above preparation process: the mass ratio of deionized water, modified porous alumina, styrene acrylate copolymer particles, sodium carboxymethyl cellulose, PVDF, and polyvinyl alcohol is 10:2:2:0.2:0.5:0.2; S7. Pump the slurry into a matrix-type dot coating structure, apply the slurry on one side of the polyolefin base film by dot coating, dry at 80° C. for 10 min, obtain a coating on the base film, and obtain a lithium-ion battery separator.
[0050] Example 2 S1. Add styrene acrylate copolymer particles, deionized water and ammonia water into a synthesis reactor, stir at 60°C and 30 r / min for 30 min, then add 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid and stir for 30 min, vacuum filter, wash with deionized water, and dry to obtain modified styrene acrylate copolymer particles; the mass ratio of styrene acrylate copolymer particles, deionized water, ammonia water and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.05:0.1; S2. Add deionized water and porous alumina into a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), mix and emulsify to obtain a first substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment; the vacuum degree of the vacuum environment is -0.095 MPa; S3, adding the first substance and the modified styrene acrylate copolymer particles to an emulsification tank, mixing, emulsifying, and obtaining a second substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S4, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, and obtaining a third substance; the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S5, mixing the third substance and PVDF, emulsifying, and obtaining a fourth substance; the emulsification conditions are: stirring for 40 min at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.080 MPa; S6, mixing the fourth substance and polyvinyl alcohol, emulsifying, and obtaining a slurry; the emulsification conditions are: stirring for 30 min at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; In the above preparation process: the mass ratio of deionized water, porous alumina, modified styrene acrylate copolymer particles, sodium carboxymethyl cellulose, PVDF, and polyvinyl alcohol is 10:2:2:0.2:0.5:0.2; S7. Pump the slurry into a matrix-type dot coating structure, apply the slurry on one side of the polyolefin base film by dot coating, dry at 80° C. for 10 min, obtain a coating on the base film, and obtain a lithium-ion battery separator.
[0051] Example 3 S1. Add porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid into a synthesis reactor, stir at 60° C. and 30 r / min for 30 min, and then dry to obtain modified porous alumina; the mass ratio of porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.2; S2, adding styrene acrylate copolymer particles, deionized water, and ammonia water into a synthesis reactor, stirring at 60° C. and 30 r / min for 30 min, then adding 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid and stirring for 30 min, vacuum filtering, washing with deionized water, and drying to obtain modified styrene acrylate copolymer particles; the mass ratio of styrene acrylate copolymer particles, deionized water, ammonia water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.05:0.1; S3, adding deionized water and modified porous alumina into a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), mixing, emulsifying, and obtaining a first substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000r / min and a revolution speed of 50r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095MPa; S4, adding the first substance and the modified styrene acrylate copolymer particles to an emulsification tank, mixing, and emulsifying to obtain a second substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000r / min and a revolution speed of 50r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095MPa; S5, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, and obtaining a third substance; the emulsification conditions are: stirring for 30 min at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S6, mixing the third substance and PVDF, emulsifying, and obtaining a fourth substance; the emulsification conditions are: stirring for 40 min at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.080 MPa; S7, mixing the fourth substance and polyvinyl alcohol, emulsifying, and obtaining a slurry (such as Figure 1~2 The emulsification conditions are as follows: stirring for 30 min at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; In the above preparation process: the mass ratio of deionized water, modified porous alumina, modified styrene acrylate copolymer particles, sodium carboxymethyl cellulose, PVDF, and polyvinyl alcohol is 10:2:2:0.2:0.5:0.2; S8. Pump the slurry into a matrix-type dot coating structure, apply the slurry on one side of the polyolefin base film by dot coating, dry at 80° C. for 10 min, obtain a coating on the base film, and obtain a lithium-ion battery separator.
[0052] Example 4 S1. Add porous alumina, N-methylpyrrolidone and 2,5-dihydroxyterephthalic acid into a synthesis reactor, stir at 50°C and 30 r / min for 30 min, and then dry to obtain modified porous alumina; the mass ratio of porous alumina, N-methylpyrrolidone and 2,5-dihydroxyterephthalic acid is 1:50:0.5; S2, adding poly(vinyl chloride-co-vinyl acetate) particles, N,N-dimethylacetamide, and triethylamine into a synthesis reactor, stirring at 50°C and 30 r / min for 30 min, then adding 2,5-dihydroxyterephthalic acid and stirring for 30 min, vacuum filtering, washing with deionized water, and drying to obtain modified poly(vinyl chloride-co-vinyl acetate) particles; the mass ratio of poly(vinyl chloride-co-vinyl acetate) particles, N,N-dimethylacetamide, triethylamine, and 2,5-dihydroxyterephthalic acid is 1:50:0.3:0.5; S3, adding deionized water and modified porous alumina into a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), mixing, emulsifying, and obtaining a first substance; the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1800r / min and a revolution speed of 40r / min at 50°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08MPa; S4, adding the first substance and modified poly (vinyl chloride-co-vinyl acetate) particles to an emulsification tank, mixing, emulsifying, and obtaining a second substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S5, mixing the second substance and lithium carboxymethyl cellulose, emulsifying, and obtaining a third substance; the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 MPa; S6, mixing the third substance and PVDF, emulsifying, and obtaining a fourth substance; the emulsification conditions are: stirring for 40 min at a rotation speed of 2000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S7, mixing the fourth substance and polyacrylic acid, emulsifying, and obtaining a slurry; the emulsification conditions are: stirring for 30 min at a rotation speed of 1000 r / min and a revolution speed of 50 r / min at 60° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 MPa; In the above preparation process: the mass ratio of deionized water, modified porous alumina, modified poly(vinyl chloride-co-vinyl acetate) particles, lithium carboxymethyl cellulose, PVDF, and polyacrylic acid is 10:2:1:0.2:0.5:0.2; S8. Coat the slurry on both sides of the polyolefin base film, dry it at 80° C. for 10 min, obtain a coating on the base film, and obtain a lithium-ion battery separator.
[0053] Example 5 S1. Add porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid into a synthesis reactor, stir at 60° C. and 30 r / min for 30 min, and then dry to obtain modified porous alumina; the mass ratio of porous alumina, deionized water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.2; S2, adding styrene acrylate copolymer particles, deionized water, and ammonia water into a synthesis reactor, stirring at 60° C. and 30 r / min for 30 min, then adding 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid and stirring for 30 min, vacuum filtering, washing with deionized water, and drying to obtain modified styrene acrylate copolymer particles; the mass ratio of styrene acrylate copolymer particles, deionized water, ammonia water, and 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid is 1:10:0.05:0.1; S3, adding deionized water and modified porous alumina into a centrifugal vacuum emulsification tank (Wenzhou Tianwo Machinery Technology Co., Ltd.), mixing, emulsifying, and obtaining a first substance; the emulsification conditions are: stirring for 40 minutes at a rotation speed of 2000r / min and a revolution speed of 50r / min at 60°C and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095MPa; S4, adding the first substance and the modified styrene acrylate copolymer particles to an emulsification tank, mixing, emulsifying, and obtaining a second substance; the emulsification conditions are: stirring for 30 minutes at a rotation speed of 1800 r / min and a revolution speed of 40 r / min at 50° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 MPa; S5, mixing the second substance and sodium carboxymethyl cellulose, emulsifying, and obtaining a third substance; the emulsification conditions are: stirring for 20 minutes at a rotation speed of 800 r / min and a revolution speed of 40 r / min at 50° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 MPa; S6, mixing the third substance and PVDF, emulsifying, and obtaining a fourth substance; the emulsification conditions are: stirring for 30 min at a rotation speed of 1800 r / min and a revolution speed of 40 r / min at 50° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.095 MPa; S7, mixing the fourth substance and polyacrylic acid, emulsifying, and obtaining a slurry; the emulsification conditions are: stirring for 20 minutes at a rotation speed of 800 r / min and a revolution speed of 40 r / min at 50° C. and a vacuum environment, and the vacuum degree of the vacuum environment is -0.08 MPa; In the above preparation process: the mass ratio of deionized water, modified porous alumina, modified styrene acrylate copolymer particles, sodium carboxymethyl cellulose, PVDF, and polyacrylic acid is 10:1:1:0.2:0.5:0.2; S8. Pump the slurry into a matrix-type dot coating structure, apply the slurry on one side of the polyolefin base film by dot coating, dry at 80° C. for 10 min, obtain a coating on the base film, and obtain a lithium-ion battery separator.
[0054] Example 6 The only difference from Example 3 is that the mass ratio of deionized water, modified porous alumina, modified styrene acrylate copolymer particles, sodium carboxymethyl cellulose, PVDF, and polyvinyl alcohol is 10:1.5:1.5:0.2:0.5:0.2.
[0055] Example 7 The only difference from Example 3 is that the porous alumina is replaced by an equal amount of non-porous alumina.
[0056] Example 8 The only difference from Embodiment 3 is that step S6 is not performed.
[0057] Example 9 The only difference from Embodiment 3 is that step S7 is not performed.
[0058] Comparative Example 1 The only difference from Embodiment 3 is that step S3 is not performed.
[0059] Comparative Example 2 The only difference from Embodiment 3 is that step S4 is not performed.
[0060] Diaphragm performance test: (1) Test the thickness according to the method in GB / T 36363-2018 and calculate the thickness increment, i.e. the coating thickness, according to the following formula; Thickness increase = battery separator thickness - base film thickness; (2) Test the liquid absorption rate and liquid retention rate according to the method in QB / T 2303.11-2008; (3) Test wettability according to the method in QB / T 2303.11-2008; Wettability is used to characterize the affinity between the separator and the electrolyte. The larger the wettability value, the better the wettability and the stronger the liquid absorption and retention, which can make the internal resistance of the battery lower; The calculation formula of wettability v is: v = h / t, where h is the wetting height (the height of the electrolyte penetrating in the vertical direction of the diaphragm), the unit is mm, and t is the wetting time, the unit is min; The electrolyte used in the wettability test is a mixture of electrolyte and solvent, the electrolyte in the electrolyte is lithium hexafluorophosphate, the solvent in the electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1), and the concentration of the electrolyte in the electrolyte is 1 mol / L; (4) Test ionic conductivity according to the method in GB / T 36363-2018, with the test temperature at 40°C and relative humidity at 48%; (5) Electrode piece adhesion test: When the electrode piece is one of a positive electrode piece and a negative electrode piece, the positive electrode piece adhesion test is performed when the electrode piece is a positive electrode piece, and the negative electrode piece adhesion test is performed when the electrode piece is a negative electrode piece; Hot-pressed positive electrode sheet adhesion: the size of the cut diaphragm is 25mm×150mm, and the size of the positive electrode sheet is 25mm×150mm; the temperature of the hot press is adjusted to 80°C, the pressure is 1000kg, and the diaphragm and the positive electrode sheet are preheated for 1s and hot pressed for 1s by the hot press; the hot-pressed positive electrode sheet adhesion is tested using an electronic tensile testing machine, and the diaphragm and the positive electrode sheet are peeled off until the stretching distance of the electronic tensile testing machine is 50mm, the speed of the electronic tensile testing machine is 300mm / min, and the peeling degree is 180°; Hot-pressed positive electrode bonding force = peeling force ÷ stretching distance of electronic tensile testing machine; Peeling force: The average force collected by the electronic tensile tester during the process of peeling the separator and the positive electrode. The hot pressing positive electrode adhesion test is calculated based on the data of the stretching distance between 10 and 40 mm, that is, the hot pressing positive electrode adhesion = peeling force between the stretching distance of 10 and 40 mm ÷ 30 mm. The positive electrode is ternary lithium nickel cobalt aluminum oxide, and the chemical formula of ternary lithium nickel cobalt aluminum oxide is LiNi 0.8 Co 0.15 Al 0.05 O2; The hot pressing negative electrode sheet adhesion test is the same as above, and the negative electrode sheet is a carbon-based graphite sheet with a carbon content of 91wt%; The test results are recorded in Table 1.
[0061] Table 1 Test results of various performances of diaphragm
[0062] It can be seen from Table 1 that the diaphragm with a polymer-ceramic integrated lithium battery diaphragm coating provided by the present invention has a liquid absorption rate of more than 110.3%, a liquid retention rate of more than 103.3%, a wettability of more than 0.1003 mm / min, an ion conductivity of more than 1.508 mS / cm, and an adhesion force with the positive electrode sheet of more than 7.1 N / m and an adhesion force with the negative electrode sheet of more than 6.0 N / m. It has good wetting properties with the electrolyte and good adhesion properties with the electrode sheets.
[0063] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Polymer-ceramic integrated lithium battery separator coating, characterized in that: Comprising modified ceramics and polymers; or, comprising ceramics and modified polymers; or, comprising modified ceramics and modified polymers; The modifiers in the modified ceramic and the modified polymer each independently include an aromatic ring compound containing a hydroxyl group and a carboxyl group.
2. The polymer-ceramic integrated lithium battery separator coating according to claim 1, characterized in that: It also includes at least one of the following features: a thickener, a binder.
3. The polymer-ceramic integrated lithium battery separator coating according to claim 1, characterized in that: It includes modified ceramics and modified polymers with a mass ratio of 1:2 to 2:
1.
4. The polymer-ceramic integrated lithium battery separator coating according to claim 1, characterized in that: When modified ceramics are included, the raw materials of the modified ceramics include ceramics and modifiers in a mass ratio of 1:0.1-0.5; When a modified polymer is included, the raw materials of the modified polymer include a polymer and a modifier in a mass ratio of 1:0.05-0.
5.
5. The polymer-ceramic integrated lithium battery separator coating according to claim 1, characterized in that: The aromatic ring compound containing hydroxyl and carboxyl groups includes one or more of 2,2'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxylic acid, 2,5-dihydroxyterephthalic acid, 4,5-dihydroxyisophthalic acid, and 4,4'-oxybis(3-hydroxybenzoic acid).
6. The polymer-ceramic integrated lithium battery separator coating according to claim 1, characterized in that: When a modified ceramic is included, the ceramic in the modified ceramic includes porous ceramic and / or non-porous ceramic; When a modified polymer is included, the polymer in the modified polymer includes one or more of styrene acrylate copolymer particles, polymethyl methacrylate particles, poly(vinyl chloride-co-vinyl acetate) particles, polyethylene particles, and polyacrylic acid particles.
7. The polymer-ceramic integrated lithium battery separator coating according to claim 4, characterized in that: When modified ceramics are included, the raw materials of the modified ceramics also include a solvent; When a modified polymer is included, the raw materials of the modified polymer also include a solvent and an alkaline auxiliary agent; The solvent in the raw material of the modified ceramic and the solvent in the raw material of the modified polymer each independently include one or more of water, N,N-dimethylacetamide, N-methylpyrrolidone, hexamethylphosphoramide, 1,4-dioxane, diglyme, and N,N-dimethylformamide; The alkaline auxiliary agent includes one or more of ammonia water, dimethylamine, triethylamine, aniline and pyridine.
8. The method for preparing a polymer-ceramic integrated lithium battery separator coating according to any one of claims 1 to 7, characterized in that: When modifying ceramics and polymers, the following steps are involved: S1, mixing the modified ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; S6, coating the slurry on the surface of the base film, and drying to obtain a polymer-ceramic integrated lithium battery separator coating; When ceramic and modified polymer are involved, the following steps are involved: S1, mixing ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the modified polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; S6, coating the slurry on the surface of the base film, and drying to obtain a polymer-ceramic integrated lithium battery separator coating; When including modified ceramics and modified polymers, the following steps are included: S1, mixing the modified ceramic and water, performing a first emulsification, and obtaining a first substance; S2, mixing the first substance and the modified polymer, and performing a second emulsification to obtain a second substance; S3, mixing the second substance and the thickener, and performing a third emulsification to obtain a third substance; S4, mixing the third substance and PVDF, and performing a fourth emulsification to obtain a fourth substance; S5, mixing the fourth substance and the binder, and performing a fifth emulsification to obtain a slurry; S6. Apply the slurry on the surface of the base film and dry it to obtain a polymer-ceramic integrated lithium battery separator coating.
9. A battery separator, characterized in that: The invention comprises a base film and a polymer-ceramic integrated lithium battery separator coating according to any one of claims 1 to 7 or a polymer-ceramic integrated lithium battery separator coating prepared by the preparation method according to claim 8, which is arranged on at least one side of the base film.
10. A battery, characterized in that: It comprises the polymer-ceramic integrated lithium battery separator coating as described in any one of claims 1 to 7, or the polymer-ceramic integrated lithium battery separator coating prepared by the preparation method as described in claim 8, or the battery separator as described in claim 9.
Citation Information
Patent Citations
Organic / inorganic composite diaphragm and preparation method therefor
CN106505172A
Battery diaphragm, preparation method thereof, lithium ion battery and electric vehicle
CN110660947A
Composite diaphragm, preparation method thereof and lithium ion battery
CN114927831A
Diaphragm and preparation method and application thereof
CN116190915A
Multilayer nanoporous separator
US20200266414A1